2021
DOI: 10.1021/acs.jpclett.0c03545
|View full text |Cite
|
Sign up to set email alerts
|

Density Sensitivity of Empirical Functionals

Abstract: Empirical fitting of parameters in approximate density functionals is common. Such fits conflate errors in the self-consistent density with errors in the energy functional, but density-corrected DFT (DC-DFT) separates these two. We illustrate with catastrophic failures of a toy functional applied to H 2 + at varying bond lengths, where the standard fitting procedure misses the exact functional; Grimme's D3 fit to noncovalent interactions, which can be contaminated by large density errors such as in the WATER27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(153 citation statements)
references
References 57 publications
5
147
1
Order By: Relevance
“…50,51 In this context, it has recently been shown that using the Hartree-Fock density in the density-corrected DFT formalism (DC-DFT) mitigates density-driven errors, particularly in the case of nonempirical functionals, because the standard fitting procedures for empirical functionals conflate density-driven errors with functional-driven errors. 62 In this study, we have demonstrated that the density-corrected SCAN (DC-SCAN) functional effectively removes density-driven errors from the water 2-body energies, which brings both binding and interaction energies of different water clusters very close to reference values calculated at CCSD(T)/CBS level of theory. Although not as pronounced as for the 2-body energies, the density correction also reduces density-driven errors in all higher-body terms of the many-body expansion (MBE) of the energy calculated for water using the DC-SCAN functional, with each individual many-body term being in quantitative agreement with the corresponding CCSD(T)/CBS reference values.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…50,51 In this context, it has recently been shown that using the Hartree-Fock density in the density-corrected DFT formalism (DC-DFT) mitigates density-driven errors, particularly in the case of nonempirical functionals, because the standard fitting procedures for empirical functionals conflate density-driven errors with functional-driven errors. 62 In this study, we have demonstrated that the density-corrected SCAN (DC-SCAN) functional effectively removes density-driven errors from the water 2-body energies, which brings both binding and interaction energies of different water clusters very close to reference values calculated at CCSD(T)/CBS level of theory. Although not as pronounced as for the 2-body energies, the density correction also reduces density-driven errors in all higher-body terms of the many-body expansion (MBE) of the energy calculated for water using the DC-SCAN functional, with each individual many-body term being in quantitative agreement with the corresponding CCSD(T)/CBS reference values.…”
Section: Discussionmentioning
confidence: 90%
“…While the search for the "optimal" XC functional for water has been, in most cases, guided by evaluating the accuracy of a given functional based on its construction and/or its ability to reproduce experimental data, 43,44,52,[87][88][89][90] more complete assessments, which also include an understanding of density-driven errors, have shed light on both merits and shortcomings of existing XC functionals at the fundamental level. 46,47,50,51,59,62,91,92 In particular, the recent development of the nonempirical SCAN functional has sparked renewed interest in ab initio simulations of water since, by satisfying all 17 known constraints for meta-GGA functionals, it largely reduces functional-driven errors. 41,42 However, as all GGA and meta-GGA functionals, SCAN still suffers from density-driven errors that are intrinsic to computationally-efficient semilocal density functional approximations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for practical reasons and due to the fact that HF is SIE free, it has been suggested to use HF densities as a reliable proxy for exact densities in DC-DFT. 120,121,127,253,254 In this section, we exemplify the impact of the DC-DFT procedure for ten systems, some of which show large and other small binding strengths; see SI for all systems and numbers (Tables S12-S19). Fig.…”
Section: A Brief Analysis Of Density-driven Errorsmentioning
confidence: 99%
“…We recommend Ref. 253 for a very recent discussion on the topic of density errors and their impact on dispersion-corrected DFT results.…”
Section: A Brief Analysis Of Density-driven Errorsmentioning
confidence: 99%